(untitled) (Balneo and PRM Research Journal, 2024)
Sufficient physical activity after breast cancer treatment is crucial for improvement of a wide range of health-related outcomes and survival. The first aim of this pilot study was to explore whether adding supervised hydrotherapy sessions to a standard 12-week exercise program consisting of already two supervised sessions of land-based exercises has beneficial effects on physical and mental functioning and quality of life in breast cancer survivors. As a secondary aim, the added value of a third supervised training session with land-based exercises to the same standard exercise program was investigated. Breast cancer patients who finished primary cancer treatment were allocated to one of the three 12-week exercise programs, i.e. a standard exercise program with two supervised land-based exercise sessions per week (control group) or the same standard program with an additional weekly supervised hydrotherapy session (hydrotherapy-group) or land-based exercise session (land-based exercise group). The efficacy of the three programs was tested by comparing changes in physical and mental functioning and quality of life from pre- until post-intervention. Twenty-six (41%) patients were allocated to the control group, 21 (33%) to the hydrotherapy-group and 16 (26%) to the land-based exercise group. The results show no differences in any outcome between the three groups. Comparing the two exercise programs with three supervised sessions, results show a significantly larger improvement in the self-reported moderate (median (IQR) +1240 (412;3330) vs. +50(-1088;1125);p=0.020) and total physical activity level (+2982 (878;5457) vs. +370(-576;1718);p=0.008) in the hydrotherapy-group compared to the land-based exercise group. The opposite was found for the outcome ‘physical symptoms’, a subscale from the health-related quality of life questionnaire with a larger improvement in the land-based exercise group compared to the hydrotherapy-group (+3(0.6;4.8) vs. +0.6(-0.8;2.1); p=0.008). In conclusion, the results of this pilot study indicate that adding a third weekly supervised session to a 12-week exercise program consisting of already two weekly supervised sessions had no added value for the improvement of physical and mental functioning and quality of life after breast cancer treatment. If a third supervised session is organized, hydrotherapy may be a valuable exercise modality since moderate and total physical activity levels seem to improve more compared to an exercise program with three supervised land-based exercise sessions. For self-reported physical symptoms although, a land-based exercise program seems more beneficial. Because of the limited sample size and pilot study design all obtained findings need to be interpreted with caution.